High molecular weight improves microstructure and mechanical properties of polyacrylonitrile based carbon fibre precursor. (28th April 2022) - Kaur, Jasjeet; Hillbrick, Linda; Abbott, Andrew; Lynch, Peter; Mota-Santiago, Pablo; Pierlot, Anthony P.
Abstract: This work presents the influence of polyacrylonitrile (PAN) molecular weight (MW) on the microstructure and macrostructure of PAN based carbon fibre precursor while fixing the PAN solution viscosity to achieve identical spinning. The impact of molecular weight on macrostructure was reported by cross sectional shape, fibre density, shear viscosity, mechanical properties and microstructure evolution was reported by void size, shape, and crystallinity. The study was carried out in the PAN MW range between 141 and 503 Kgmol -1 . The PAN fibre strength improvement of 5–9 cNdtex −1 with increasing PAN MW is caused by the drop in PAN fibril size from 24 nm at 141 Kgmol -1 to 18 nm at 503 Kgmol -1 . The improvement in PAN fibre density from 1.14 to 1.18 gcm −3 with increasing PAN MW is caused by the improved microstructure alignment from 15 o to 8 o and is the driving force for increased mechanical modulus from 115 to 150 cNdtex −1 . Graphical abstract: Image 1 Highlights: ⁃ Increase in polyacrylonitrile molecular weight increases density, tenacity, and modulus of carbon fibre precursors ⁃ The polyacrylonitrile (PAN) fibre strength improvement is caused by the drop in PAN fibril size ⁃ The enhancement in polyacrylonitrile fibre density and modulus is caused by the improved microstructure alignment ⁃ The macroscopic diameter change in fibres from the wash bath to the end of the line, was accommodated by void contraction